Severity and workload of nursing with patients seeking admission to an intensive care unit - Meire Cristina Novelli e Castro; Magda Cristina Queiroz Dell'Acqua; Igor Chagas Unger; Claudia Maria Silva Cyrino; Priscila Masquetto Vieira de Almeida (Universidade Federal do Rio de Janeiro, 2017)
Abstract Objective: To identify the severity and workload of nursing with adult patients seeking admission to an Intensive Care Unit (ICU). Methods: A cross-sectional study with a quantitative, exploratory and prospective approach was performed, developed in a hospital in the state of São Paulo. Demographic data on patients were collected, the Simplified Acute Physiology Score III (SAPS III) was applied to assess the severity of patients and the Nursing Activities Score (NAS) was used to evaluate nursing workload, between July and August 2014. Results: The overall mean score of the SAPS III was 30.52 ± 18.39 and that of the NAS was 58.18 ± 22.29. The group of patients admitted to the ICU showed higher severity and higher workload of nursing compared to non-admitted patients. Non-admitted patients had an NAS of 53.85. Conclusion: The nursing workload in patients who were not admitted to the ICU was also high. The evaluation of workload in other contexts where patients are seriously ill is important. The workload assessment in other contexts where severely ill patients are found is evident.